The Relationship Between Health-Related Quality of Life and Saliva C-Reactive Protein and Diurnal Cortisol Rhythm in Latina Breast Cancer Survivors and Their Informal Caregivers: A Pilot Study. (July 2021) - Pace, Thaddeus W. W.; Badger, Terry A.; Segrin, Chris; Sikorskii, Alla; Crane, Tracy E.
Introduction: To date, no study has explored associations between objective stress-related biomarkers (i.e., inflammatory markers, diurnal rhythm of cortisol) and health-related quality of life (HRQOL) in Latina breast cancer survivors and their informal caregivers (i.e., family, friends).Method: This cross-sectional feasibility study assessed saliva C-reactive protein, saliva diurnal cortisol rhythm (cortisol slope), and self-reported HRQOL (psychological, physical, and social domains) in 22 Latina survivor–caregiver dyads. Feasibility was defined as ≥85% samples collected over 2 days (on waking, in afternoon, and in evening). Associations between biomarkers and HRQOL were examined with correlational analyses.Results: Collection of saliva was feasible. Strongest associations were observed between survivor evening cortisol (as well as cortisol slope) and fatigue, a component of physical HRQOL.Discussion: Associations presented may help promote investigations of mechanisms linking stress-related biomarkers and HRQOL in Latina breast cancer survivor–caregiver dyads, which will facilitate development of culturally congruent interventions for this underserved group.